New Keynesian versus old Keynesian government spending multipliers - John F. Cogan; Tobias J. Cwik; John B. Taylor; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
Renewed interest in fiscal policy has increased the use of quantitative models to evaluate policy. Because of modeling uncertainty, it is essential that policy evaluations be robust to alternative assumptions. We find that models currently being used in practice to evaluate fiscal policy stimulus proposals are not robust. Government spending multipliers in an alternative empirically-estimated and widely-cited new Keynesian model are much smaller than in these old Keynesian models; the estimated stimulus is extremely small with GDP and employment effects only one-sixth as large.
urn:nbn:de:hebis:30-68369
Keywords: C52; E62; 330; Fiscal Multiplier; New Keynesian Model; Fiscal Stimulus; Government Spending; Macroeconomic Modeling; Finanzpolitik; Öffentliche Ausgaben; Keynesianismus; Multiplikator; Schätzung; USA